Thirty years after Alma-Ata: a systematic review of the impact of community health workers delivering curative interventions against malaria, pneumonia and diarrhoea on child mortality and morbidity in sub-Saharan Africa - Lewin Simon; Le May Alex; Christopher Jason B; Ross David A (BMC, 2011)
Abstract Background Over thirty years have passed since the Alma-Ata Declaration on primary health care in 1978. Many governments in the first decade following the declaration responded by developing national programmes of community health workers (CHWs), but evaluations of these often demonstrated poor outcomes. As many CHW programmes have responded to the HIV/AIDS pandemic, international interest in them has returned and their role in the response to other diseases should be examined carefully so that lessons can be applied to their new roles. Over half of the deaths in African children under five years of age are due to malaria, diarrhoea and pneumonia - a situation which could be addressed through the use of cheap and effective interventions delivered by CHWs. However, to date there is very little evidence from randomised controlled trials of the impacts of CHW programmes on child mortality in Africa. Evidence from non-randomised controlled studies has not previously been reviewed systematically. Methods We searched databases of published and unpublished studies for RCTs and non-randomised studies evaluating CHW programmes delivering curative treatments, with or without preventive components, for malaria, diarrhoea or pneumonia, in children in sub-Saharan Africa from 1987 to 2007. The impact of these programmes on morbidity or mortality in children under six years of age was reviewed. A descriptive analysis of interventional and contextual factors associated with these impacts was attempted. Results The review identified seven studies evaluating CHWs, delivering a range of interventions. Limited descriptive data on programmes, contexts or process outcomes for these CHW programmes were available. CHWs in national programmes achieved large mortality reductions of 63% and 36% respectively, when insecticide-treated nets and anti-malarial chemoprophylaxis were delivered, in addition to curative interventions. Conclusions CHW programmes could potentially achieve large gains in child survival in sub-Saharan Africa if these programmes were implemented at scale. Large-scale rigorous studies, including RCTs, are urgently needed to provide policymakers with more evidence on the effects of CHWs delivering these interventions.